[-6 (multiplied by) 2] = -12
[19 (multiplied by) -10] = -190
-12 + -190 = -202
2007-04-03 08:05:00
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
If you are stating negative six times two plus nineteen times x minus ten then this expression can be simplified to -12+19x-10 and can be further simplified to -2+19x or 19x-2
2007-04-03 15:16:10
·
answer #2
·
answered by Danyal Ali 1
·
0⤊
0⤋
-6x^2 + 19x -10 Multiply by -1
6x^2 -19x + 10 Now factor
(3x -2) (2x -5)
To solve for x set each factor = to 0
2007-04-03 15:08:49
·
answer #3
·
answered by kale_ewart 5
·
0⤊
0⤋
I assume you mean -6x^2 + 19x - 10 = 0
just put into the equation
x = (-19 +- sqrt(19^2 - 240))/ -12
x = (1/12) * (19 +- 11)
= 2/3 or 2.5
2007-04-03 15:07:35
·
answer #4
·
answered by biglildan 6
·
0⤊
0⤋
-6*2+19*(-10) = -12-190= -202
OR:
-6x^2 + 19x - 10 = (-3x + 2)(2x - 5)
2007-04-03 15:07:02
·
answer #5
·
answered by jimvalentinojr 6
·
0⤊
0⤋
If you want to factor this, it is -(2x-5)(3x-2). If you want to solve for x when you set it equal to 0, the factored form makes it clear that x=5/2 or x=2/3.
2007-04-03 15:05:03
·
answer #6
·
answered by steve112285 3
·
0⤊
0⤋
is that -6x + 19x - 10??? i could help is you wrote it a bit more clearly
2007-04-03 15:04:34
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
What are you trying to do with this expression?
2007-04-03 15:02:54
·
answer #8
·
answered by bruinfan 7
·
0⤊
0⤋